Introducing the interpretation of medieval Hindī texts into the Hindī curriculum: An alternative approach - Strnad, Jaroslav (Acta Orientalia Vilnensia, 2008)
Oriental Institute of the Czech Academy of SciencesThe author has been trying, for several years now, to apply and further expand the method of detailed morphological analysis of Old Hindī texts first developed by the Czech Indologist Vladimir Miltner in his Old Hindī Reader and to test it in the courses given at the Institute of Indology at Charles University, Prague. This paper demonstrates the possibilities this still little used descriptive approach offers to students who have basic knowledge of Modern Standard Hindī and wish to gain an insight into the grammatical structure of Old Hindī literary dialects. Careful use of this method helps highlight, among other things, the high degree of homonymy of grammatical morphemes and the consequent frequent ambiguity of meaning. A continuous text segmented into basic morphological units can be processed by a concordancing software and further analysed with the help of methods developed in the field of corpus linguistics. An appendix to the paper shows the method as applied to the analysis of one short pad (poem) of a medieval Hindī poet, Sant Kabīr.The use of this method in classes helps the students read and interpret a greater quantity of texts in a relatively short time. This can serve as an incentive on the one hand to work with the literary material in the source language and on the other to pay closer attention to distinctive features of written and oral traditions in their wider social contexts.